Pelvic Inflammatory Disease During the Post-Partum Year - Barry P. Katz; Marc B. Rosenman; Jane Wang; M'hamed Temkit; Barbara E. Mahon (Hindawi Limited, 2005)
Objective. To investigate the occurrence of, and risk factors for, pelvic inflammatory disease (PID) occurring during the post-partum year.